A Study on Causes of Condemnation of Carcass and Organs at Shah Alam Abattoir - Tham, K. M.; Abdul Rahman, Sheikh Omar (1981)
A two-week study of the causes of condemnation at Shah Alam abattoir was conducted. In the bovine species, liver and lungs w.ere the main organs condemned due to fluke infestation. and emphysema respectively. Ninety-five percent of pig lungs were condemned because of back bleeding, while in sheep caseous lymphadenitis was the major cause of organ condemnedtion affectingg mainly the lungs and lymph nodes. No total carcass condemnation was observed in any species during the study period